Effect of Epidermal Growth Factors (EGF) on the Maturation and Developmental Competence of Buffalos’ Oocytes and Embryo Stages In Vitro - Nasra Ahmed Yousef (South Valley University, 2018)
The present study aims to study the effects of epidermal growth factors (EGF) supplementations to the in vitro maturation (IVM) medium of buffalo's oocytes on the oocyte maturation rate and embryo development competence. The ovaries were collected from El-Monieb slaughters house and transferred directly to the laboratory for the experiment processing. Excellent and good cumulus oocytes complexes (COCs) were aspirated from 3-8 mm diameter follicles. TCM-199 medium were used for in vitro maturation. In experiment I, COCs were incubated in EGF-containing IVM medium as; 0 (control or CTL), 10, 20 and 50 ng/ml EGF for 24 hrs at 38.5°C in humidified environment; 5% CO2 and 95% humidity. In experiment II, COCs were incubated in vitro fertilization (IVF) medium as; 0 (control or CTL), 10, 20 and 50 ng/ml EGF for 24 hrs in the same condition. In experiment III, COCs were incubated in vitro culture (IVC) medium as; 0 (control or CTL), 10, 20 and 50 ng/ml EGF for 24 hrs in the same condition. According to the expansion of oocytes and attaining the developmental embryo stages of morula and blastocyst, our results have shown that addition of 20 ng/ml of EGF to the IVM medium significantly increased the oocyte maturation and fertilization rates compared to those of CTL (76.96 ± 9.04 vs. 51.3 ± 4.66 and 67.96 ± 2.76 vs. 42.03 ± 4.83 %, respectively) (P<0.05). On the other hand, Addition of 20 ng/ml of EGF to the IVM medium significantly increased the fertilization rates compared to other concentrations (10 and 50 ng/ml) (67.96 ± 02.76 vs. 49.43 ± 03.67 and 34.70 ± 01.40, respectively). However, the developmental rates to morula and blastocyst stages in response to addition to IVC medium variably increased rather than those of control despite no significance.